2009
DOI: 10.1021/pr800772b
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Epithelial Cell Proteome from Wild-Type and TNFΔARE/WT Mice: Effect of Iron on the Development of Chronic Ileitis

Abstract: Environmental factors substantially contribute to the development of chronic intestinal inflammation in the genetically susceptible host. Nutritional components like iron may act as pro-oxidative mediators affecting inflammatory processes and cell stress mechanisms. To better characterize effects of dietary iron on epithelial cell responses under the pathological conditions of chronic intestinal inflammation, we characterized the protein expression profile (proteome) in primary intestinal epithelial cells (IEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 67 publications
0
18
0
1
Order By: Relevance
“…Functional proteome analysis of primary ileal IECs from wild-type (WT) and TNF ∆ARE/WT mice fed an iron sulfate containing diet or iron sulfate free diet revealed significant differences in the regulation of proteins participating in energy metabolism and stress responses when comparing inflamed with non-inflamed conditions 10. In this study, we used heterozygous TNF ∆ARE/WT mice to investigate the mechanistic role of both luminal iron sulfate and systemic iron in the development of chronic ileitis in a model of Crohn's disease focussing on the effect of iron status on ER stress regulation and changes in gut microbial ecology.…”
Section: Introductionmentioning
confidence: 99%
“…Functional proteome analysis of primary ileal IECs from wild-type (WT) and TNF ∆ARE/WT mice fed an iron sulfate containing diet or iron sulfate free diet revealed significant differences in the regulation of proteins participating in energy metabolism and stress responses when comparing inflamed with non-inflamed conditions 10. In this study, we used heterozygous TNF ∆ARE/WT mice to investigate the mechanistic role of both luminal iron sulfate and systemic iron in the development of chronic ileitis in a model of Crohn's disease focussing on the effect of iron status on ER stress regulation and changes in gut microbial ecology.…”
Section: Introductionmentioning
confidence: 99%
“…Iron-induced oxidative stress in the intestinal lumen showed far-reaching metabolic consequences in a murine model of Crohn’s disease [28,29]. It induces endoplasmic reticulum stress, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical study revealed that targeted therapy against TNF-α could downregulate epithelial cell apoptosis and promotes barrier repair in active Crohn's disease [26]. Mutant mouse with TNF-α overexpression may cause IEC FFA (fumarylacetoacetate) accumulation [27], which has been proven as a potent inducer of ER stress [28]. Since whether TNF-α alone could induce ER stress and apoptosis is controversial in vitro [29], and previous studies revealed that IFN-γ prime the response of Caco-2 cells to TNF-α through induction of TNFR2 expression [15] or potentiating TNF-related apoptosis-inducing ligand [30], a combination of IFN-γ and TNF-α was used.…”
Section: Discussionmentioning
confidence: 99%